2022
DOI: 10.1002/jemt.24127
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and anatomical traits during development: Highlighting extrafloral nectaries in Passiflora organensis

Abstract: Passiflora organensis is a small herbaceous vine with characteristic morphological variations throughout its development. The plant bears button-shaped extrafloral nectaries exclusively in adult leaves. Extrafloral nectaries are structures that secrete nectar and play an important role in plant-animal interactions as a strategy for protecting plants against herbivory. In this work, we performed anatomical and ultrastructural studies to characterize P. organensis extrafloral nectaries during their secretory pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…4b-c). Although all three characteristic nectary tissues (nectary epidermis, nectariferous parenchyma, and subnectariferous parenchyma; Cardoso-Gustavson et al, 2013; Macêdo et al, 2021; Moraes et al, 2022) were observed in Pe NT and Pe OE plants (Fig. 4d-f), the number of cells in each layer was strongly reduced in these plants (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…4b-c). Although all three characteristic nectary tissues (nectary epidermis, nectariferous parenchyma, and subnectariferous parenchyma; Cardoso-Gustavson et al, 2013; Macêdo et al, 2021; Moraes et al, 2022) were observed in Pe NT and Pe OE plants (Fig. 4d-f), the number of cells in each layer was strongly reduced in these plants (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…2), suggesting that the ontogeny of these structures was affected by low SPL expression and that changes in leaf development affect the growth of EFNs. Although the morphology of EFNs was affected in miR156-OE Passiflora plants, their tissue patterning was similar to NT plants, with demarcated nectary epidermis and nectariferous and subnectariferous parenchyma (Lemos et al, 2017; Moraes et al, 2022). However, cell number was strongly reduced mostly in the parenchymatic tissues (Fig.4m, n).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations